Digital Texts and Diagrams: Representing the Transmission of Euclid’s Elements - Christine Roughan (Digital Classics Online)
The Digital Euclid project aims to publish an open, digital edition of every extant witness to the text and diagrams of Euclid’s Elements. This paper discusses the required groundwork and is divided in two parts. It first covers a survey of the surviving manuscript and print sources for the Elements that intends to identify the extent of these materials, how many of these works have already been digitally imaged, and what challenges they pose to current data extraction methods. The latter part of the paper discusses the methods used to produce machine-actionable texts and diagrams and focuses especially on the development of tools for the identification and extraction of diagrammatic data.